(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
This article analyzes the origin, formation and distribution area of previously little explored in science, but widespread state, administrative and military titles (positions) «tutuk» («tutuk») and «sangun» («sangun») in the Kyrgyz Kaganate (VI- XI centuries) and other state formations of the Eurasian space. For the first time, an attempt has been made to make a historical and linguistic analysis of previously unexplored titles (positions) used in the management of the state and its structures. From the first steps of state history, Kyrgyz society was strictly ranked. The place and political weight of a member of society was largely determined by his title, often hereditary, which consolidated the position of his bearer in the system of social ties and subordination. In the system of state administration, the Kyrgyz and their neighbors, the Kok Turks, Uighurs and other peoples, had a bureaucratic apparatus for governing the country and its possessions that was quite developed for its time. High government positions, various administrative units of the state were governed by officials with different titles.